Some issues on murabahah practices in Iran and Malaysian Islamic banks - Zandi Pour Joopari, GholamReza; Mohd. Ariffin, Noraini (2011)
Purpose – The purpose of this paper is to analyze the nature of Murabahah contract in the fully grounded Islamic banking system i.e., Iran and Malaysia. Design/methodology/approach – The approach taken is descriptive. Findings – Although the main principle of Islamic financial institutions is prohibition of usury, it is surprised to see that Islamic financial institutions are still practicing usury in their transaction as evidenced in Iran. In the case of Malaysia however, BBA home financing is used by Islamic financial institutions and the profit rate is still dependent on the market interest rate due to arbitrage activities. Research limitation/implications – There is no transparent framework for Murabahah contract in Islamic banks. Indeed there is a need for the banking standard regulators to set a clear and disciplined framework for this type of banking contract. Originality/value – The study hopes to improve the overall competency and reliability of the Islamic banking system in the world. The finding of this study will be a basis for further research in Murabaha with respect to the regulatory environment and Shari’ah compliance in particular in Iran.